Predominant expression of truncated EpCAM is associated with a more aggressive phenotype and predicts poor overall survival in colorectal cancer. Issue 3 (15th April 2016) - Seeber, Andreas; Untergasser, Gerold; Spizzo, Gilbert; Terracciano, Luigi; Lugli, Alessandro; Kasal, Armin; Kocher, Florian; Steiner, Normann; Mazzoleni, Guido; Gastl, Guenther; Fong, Dominic
Abstract : Regulated intramembrane proteolysis (RIP) has been shown to be an important mechanism for oncogenic activation of EpCAM through nuclear translocation of the intracellular domain EpICD. Recently, we identified two different membranous EpCAM variants namely EpCAM MF (full‐length) and EpCAM MT (truncated) to be expressed in the majority of human epithelial tumors. The aim of our study was to evaluate the potential role of these two protein variants as additional prognostic biomarkers in colorectal cancer. In most studies only one antibody targeting the extracellular domain of EpCAM (EpEX) has been used, whereas in the present study additionally an antibody which detects the intracellular domain (EpICD) was applied to discriminate between different EpCAM variants. Using immunohistochemistry, we analyzed the expression of EpCAM MF and EpCAM MT variants in 640 patients with colorectal cancer and determined their correlations with other prognostic factors and clinical outcome. A statistically significant association was observed for EpCAM MT with advanced tumor stage ( p  < 0.001), histological grade ( p  = 0.01), vascular ( p  < 0.001) and marginal ( p  = 0.002) invasion. Survival analysis demonstrated reduced overall survival ( p  < 0.004) in patients with tumors expressing the EpCAM MT phenotype when compared to patients with tumors expressing the EpCAM MF variant. In conclusion, this study for the first time indicates that expression of EpCAM MT is associated with a more aggressive phenotype and predicts poor survival in patients with colorectal cancer. Abstract : What's New? Two novel cell‐adhesion molecules, the full‐length variant EpCAM MF and the truncated variant EpCAM MT, which is characterized by proteolytic cleavage of the EpCAM intracellular domain (EpICD), were recently identified on the membrane of human epithelial tumor cells. EpICD loss at the membrane is correlated with poor prognosis in pancreatic and breast cancers. Whether EpCAM MT expression, which possibly leads to EpICD loss, similarly influences tumor behavior, however, is unknown. The authors of the present study investigated the expression of EpCAM MF and EpCAM MT in colorectal cancer patients. The findings reveal an association between EpCAM MT expression, aggressive tumor behavior, and poor outcome in colorectal cancer.